การประเมินโครงการการจัดกิจกรรมการเรียนรู้หลักปรัชญาของเศรษฐกิจพอเพียง ตามแนวทางศาสตร์พระราชาของโรงเรียนบ้านซิแบร - สุขสวัสดิ์ ประเสริฐ (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2022)
บทคัดย่อ การวิจัยครั้งนี้เป็นการวิจัยเชิงประเมิน มีวัตถุประสงค์เพื่อประเมินโครงการการจัดกิจกรรมการเรียนรู้หลักปรัชญาของเศรษฐกิจพอเพียงตามแนวทางศาสตร์พระราชาของโรงเรียนบ้านซิแบร ตามรูปแบบ CIPPIEST MODEL เป็นกรอบการประเมิน 8 ด้าน คือ 1) ด้านสภาพแวดล้อม 2) ด้านปัจจัยเบื้องต้น 3) ด้านกระบวนการ 4) ด้านผลผลิต 5) ด้านผลกระทบ 6) ด้านประสิทธิผล 7) ด้านความยั่งยืน และ 8) ด้านการถ่ายทอดส่งต่อ โดยเก็บรวบรวมข้อมูลจากผู้ทรงคุณวุฒิ จำนวน 9 คน กรรมการสถานศึกษาขั้นพื้นฐาน จำนวน 7 คน ครูผู้รับผิดชอบโครงการ จำนวน 1 คน ครูและบุคลากรทางการศึกษาในโรงเรียน 14 คน นักเรียนชั้นประถมศึกษาปีที่ 4 – มัธยมศึกษาปีที่ 2 จำนวน 143 คน และผู้ปกครองนักเรียนชั้นประถมศึกษาปีที่ 4 – มัธยมศึกษาปีที่ 2 จำนวน 87 คน รวม 261 คน ระหว่างปีการศึกษา 2562-2564 เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลได้แก่ แบบสอบถามมาตราส่วนประมาณค่า 5 ระดับ โดยประยุกต์ใช้การประเมินโครงการตามรูปแบบ CIPPIEST MODEL การวิเคราะห์ข้อมูลเมื่อเปรียบเทียบกับเกณฑ์ที่กำหนด โดยใช้ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ยและค่าส่วนเบี่ยงเบนมาตรฐาน ซึ่งนำเสนอเสนอในรูปแบบตารางประกอบการบรรยาย ผลการวิจัยพบว่า ผลการประเมินโครงการผ่านเกณฑ์ประเมินทั้ง 8 ด้าน ด้านบริบท ด้านกระบวนการ ด้านผลผลิต ด้านผลกระทบ ด้านประสิทธิผล ด้านความยั่งยืน และด้านการถ่ายทอดส่งต่อ อยู่ในระดับมากที่สุด ส่วนด้านปัจจัยอยู่ในระดับมาก คำสำคัญ: การประเมินโครงการ, หลักปรัชญาของเศรษฐกิจพอเพียง ABSTRACT This research is an assessment research. The objectives were to evaluate the project of learning activities on the philosophy of a sufficient economy according to the royal science of Ban Zibrae School by using the format CIPPIEST Model with eight aspects: 1) context, 2) input, 3) process, 4) product, 5) effect, 6) effectiveness, 7) sustainability and 8) transportability. This data was collected from 9 experts, 7 being chairmen of the basic educational school committees, 1 teacher in charge of the project, 14 teachers from educational personnel in schools, 143 Prathomsuksa 4-Matthayomsuksa 2 students and 87 Prathomsuksa 4-Matthayomsuksa 2 student’s parents, the total number were 261 respondents during the academic year 2019-2021. A tool used to collect data was a five-rating scale questionnaire used for the project evaluation based on the CIPPIEST MODEL. The data was analyzed by using frequency, percentage, mean and standard deviation and presented in tables with descriptions. The results of the evaluation found that the overall evaluation of the context of the project of learning activities on the philosophy of a sufficient economy according to the royal science of Ban Zibrae School found that it was at the highest level and passed the assessment criteria. When considering the results of the assessment in all 8 aspects: context, input, process, product, effect, effectiveness, sustainability and transportability are at the highest level. The context evaluation results are at a high level. Keywords: The Evaluation on the Context of the Project, The Philosophy of a Sufficient Economy